2014
DOI: 10.4161/psb.29204
|View full text |Cite
|
Sign up to set email alerts
|

Memristors in the Venus flytrap

Abstract: A memristor is a nonlinear element because its current-voltage characteristic is similar to that of a Lissajous pattern for nonlinear systems. We investigated the possible presence of memristors in the electrical circuitry of the Venus flytrap's upper and lower leaves. The electrostimulation of this plant by bipolar sinusoidal or triangle periodic waves induces electrical responses in the upper and lower leaves of the Venus flytrap with fingerprints of memristors. The analysis was based on cyclic voltammetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…TEACl, an inhibitor of voltage gated K C channels, transform a memristor to a resistor. 15,30,31 Plants have these voltage gated potassium ion channels associated with plasma membranes. 16 Our analytical model of a memristor in plants with a capacitor connected in parallel shows that at very high frequencies instead of a single-valued function of a memristor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…TEACl, an inhibitor of voltage gated K C channels, transform a memristor to a resistor. 15,30,31 Plants have these voltage gated potassium ion channels associated with plasma membranes. 16 Our analytical model of a memristor in plants with a capacitor connected in parallel shows that at very high frequencies instead of a single-valued function of a memristor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MTs and other cytoskeletal filaments in neurons have been hypothesized to store molecular bits of information that can build up memory at a sub-cellular level. They have also been proposed to transmit electrical signals in neuronal cells [16][17][18][19][20] . Conducting properties of AFs and MTs have been experimentally and computationally investigated yielding important insights into their remarkable behavior, which is discussed below.…”
Section: Microtubulesmentioning
confidence: 99%
“…Such generalized memristors have been identified in numerous naturally occurring systems, e.g. potassium and calcium ion channels in the Hodgkin-Huxley nerve membrane circuit model 8,9 , the aplysia habituation neuron in Kandel's research on memory 10,11 , silk proteins 12 , organic memristors 13 and conducting structures in plants [14][15][16] . The connection between memristors and neuronal synapses 17 can potentially shed light on the enigma of memory generation, erasure and retention in the human brain.…”
mentioning
confidence: 99%
“…We have found memristors in the electrical circuitry of Venus flytrap, Aloe vera and Mimosa pudica. 16,[18][19][20] Gale et al 26 found memristive properties of protoplasmic tubes of a cellular slime mold Physarum polycephalum. Johnsen et al 27 found that the sweat ducts in the skin are memristors.…”
Section: Introductionmentioning
confidence: 99%
“…Volkov et al [18][19][20][21] found that the electrostimulation of plants by bipolar periodic sinusoidal or triangle waves induces electrical responses with fingerprints of memristors of type I or type II. To elucidate this mechanism, Markin et al 16 proposed analytical models of a memristor and a memristor with a capacitor connected in parallel.…”
Section: Introductionmentioning
confidence: 99%